USE OF SMART LADDER SNAKE MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES OF IV GRADE STUDENTS OF STATE ELEMENTARY SCHOOL I DOROPAYUNG PANCUR REMBANG - Ahmad Hariyadi (Universitas Muria Kudus, 2018)
The objectives of this study are to describe the activities of teachers and students during the use of smart ladder snake learning media, as well as to describe the improvement of student learning outcomes after using snake and ladder smart learning media. This type of research was a classroom action research consisting of planning, implementation, observation, and reflection. The subject of this study was the third grade students of State Elementary School in the academic year of 2017/2018. Data collection techniques of this study were observations of teacher, student activities, and tests for student learning outcomes. The results of this study indicate that by using smart snake ladder learning media, it is enable to improve teacher activities, student activities, and students’ learning outcomes. Teacher activity cycles are increasing by 20.45%, student activity increases 27.17%, while the student learning outcomes increase 8.91. Conclusion in this study is smart snake ladder learning media is able to improve teacher activity, student activity, and students’ learning outcomes in State Elementary School I Doropayung.